Inhibition of human lymphocyte proliferation and cleavage of interleukin-2 by Pseudomonas aeruginosa proteases. - Theander, T G (1988)
This study was undertaken to determine the effect of Pseudomonas aeruginosa alkaline protease (AP) and elastase (ELA) on human lymphocyte function. AP at 50 micrograms/ml and ELA at 12 micrograms/ml caused a 50% inhibition of phytohemagglutinin-induced proliferation. There was no difference in the effect of proteases on CD4- and CD8-positive cells. To determine the effect of proteases on interleukin-2 (IL-2)-induced cell proliferation, the proteases and IL-2 were added to the IL-2-dependent CTLL-2 cell line. AP and ELA inhibited the proliferation of these cells. When IL-2 was added in excess, the inhibition was partly reversed. ELA at 10 micrograms/ml cleaved IL-2, as judged by size chromatography of a reaction mixture containing 125I-labeled IL-2 and the proteases. The ELA-digested IL-2 exhibited a reduced binding capacity to IL-2 receptors on the lymphocytes. Furthermore, treatment of phytohemagglutinin-stimulated lymphocytes with AP and ELA resulted in inhibition of binding of intact IL-2 to IL-2 receptors on the stimulated lymphocytes. These results indicated that P. aeruginosa-derived enzymes are able to interfere with human lymphocyte function in vitro and that this effect might be due to cleavage of IL-2.